Upper-Tropospheric Temperature Pattern Over the Asian-Pacific Region in CMIP6 Simulations: Climatology and Interannual Variability - Fan, Qiwei; Zhou, Botao (Frontiers in Earth Science, 2022)
Temperature is a most important indicator for climate change. However, compared to surface air temperature, relatively less attention has been shown to the upper-tropospheric temperature (UTT). Given that the Asian-Pacific UTT plays a remarkable role in the climate system, its future change deserves great attention. In this study, based on the Coupled Model Intercomparison Project phase 6 (CMIP6) simulations, the fidelity of 30 CMIP6 models on the Asian-Pacific UTT patterns was evaluated and their future changes under the scenarios of the Shared Socioeconomic Pathway (SSP) 2-4.5 and 5-8.5 were projected. The evaluation indicates that the CMIP6 models have a good capacity to reproduce the climatology and interannual variability of seasonal UTT during 1965-2014, with the multi-model ensemble mean (MME) outperforming individual models. The observed seesaw oscillation between the Asian UTT and the North Pacific UTT during four seasons, named Asian-Pacific Oscillation (APO), is also well performed. The MME projects a similar spatial change under both scenarios in the second half of the 21st century, with lager changes in magnitude under SSP5-8.5 than under SSP2-4.5. Compared to 1965-2014, during 2050-2099, spring, summer and autumn UTTs are projected to cool (warm) in a widespread area of Asia (the North Pacific). The projected winter UTT decreases in East Asia and most of the North Pacific. In addition, an increased interannual variability of seasonal UTT is anticipated particularly in the mid-low latitudes of the Asian-Pacific sector. The APO phenomenon is expected to still be dominant in the future climate, but its intensity (interannual variability) tends to weaken (enlarge) in each season as compared to the current.